Heavy metals’ effect of (copper and zinc) on the parameters: chemical, morphological, biometrical and physiological of tomato (Lycopersicon esculentum Mill.) - OSMANE, Badiâa (My University, 2021)
In agriculture, both heavy metals, copper and zinc, are used as essential elements for plants growth and development. However, the excessive amount of these elements can lead to adverse effects. In this regard, to assess the heavy metal stress responses which were occurred in leaves and roots of Lycopersicon esculentum Mill. the seedlings were subjected to different concentrations of copper and zinc: 0, 100, 200, 300, 400, and 500 ppm. Notably, the phytoxicity and mobility of the heavy metals depend mainly on their chemical forms in the soil. Thus, in the present study, the metal fractionation and chemical speciation were determined by using the Tessier sequential extraction method. At high level,copper and zinc penetrate into tomato plant tissues leading to major damages on the fundamental and physiological processes (photosynthesis, proteins biosynthesis, transpiration, and cellular water status), therefore; plant reacts rapidly and positively by operating all the mechanisms which can help it to cope against this metal stress, such as the implement of the metabolic processes (antioxidant system and osmotic adjustment). All these internal alterations result in onset of phytotoxicity symptoms, accompanied with great morphological changes such as limiting the plant growth and cell division. Furthermore, our results indicate that the proteins, osmolytes (soluble sugars and proline), antioxidant activity (DPPH), and antioxidant compounds (polyphenols and flavonoids) were highly accumulated in leaves than roots, this might be due to the high level of copper and zinc in the both tissues. The metals content in leaves and roots increased gradually by increasing of their concentration in the soil. Remarkably, zinc was highly accumulated in roots, whereas, a great content of copper was translocated to the leaves. Besides, the distribution of heavy metals in soil was predominantly detected in the organic fraction. However, a little amount was recorded in the exchangeable fraction. A positive correlation was marked between the osmoregulators and antioxidants, as well as between the metal fractions in the soil and those in the plant. In general, the tomato plant which is growing in the soil contaminated by heavy metals could be stressed depending on the level of these elements in the soil, their bioavailability, and the target plant tissue. This crop might be also suggested for the phytoremediation process due to its accumulative potential, but; this present a risk as tomato is a vegetable crop with edible fruit.
Keywords: Copper, chemical speciation, heavy metal stress, Lycopersicon esculentum Mill., zinc.